Correlation between seminal plasma biochemical markers and semen parameters in idiopathic oligoasthenoteratospermia: identification of biomarkers for L-carnitine therapy - Yuan, Qilong; Hong, Ruifang; Ni, Yunping; Jiang, Manbo; Liu, Juan; Chen, Zhiqiang; Yang, Dongyu (Frontiers in Endocrinology, 2024)
Background: L-carnitine therapy for idiopathic sperm abnormalities exhibits variable effectiveness, and currently, there are no established criteria to predict patient response. This study investigated correlations between seminal plasma markers and semen parameters to identify biomarkers that can guide indications for L-carnitine therapy indications in patients with idiopathic sperm abnormalities.A retrospective review was conducted on 223 male patients with idiopathic oligoasthenoteratospermia, who sought medical attention at our clinic between January 2020 and October 2022. These patients underwent a pretreatment seminal plasma biochemical analysis, followed by a three-month continuous L-carnitine treatment. The correlation between seminal plasma biochemical parameters and pretreatment semen parameters was analyzed. Semen quality was compared between cases with normal and abnormal seminal plasma biochemical parameters, both pretreatment and posttreatment. The correlation between the changes in semen parameters after treatment and seminal plasma biochemical parameters were investigated.Results: Correlation analyses revealed significant associations between all pretreatment semen parameters and seminal plasma biochemical markers, except for liquefying time and the ratio of normal morphology. Subgroup analysis, stratified by seminal fructose, zinc, citric acid, and neutral glycosidase levels, demonstrated that abnormal groups exhibited significantly different levels of semen parameters compared with the normal groups. The changing difference and changing ratio in the ratio of forward motile sperm showed a negative correlation with seminal fructose levels (r=-0.165 and -0.144). The changing difference in semen volume was negatively correlated with the level of seminal neutral glycosidase (r=-0.158). The changing ratio in semen volume, sperm concentration, total sperm count, and count of forward motile sperm all exhibited negative correlations with the levels of seminal neutral glycosidase (range from -0.178 to -0.224).Seminal plasma biochemical markers, particularly fructose and neutral glycosidase, may serve as valuable indicators for determining the eligibility of patients with idiopathic sperm abnormalities for L-carnitine therapy.